Congenital disorders of N-glycosylation - Schachter, Harry (Henry Stewart Talks, 2012)
Orphan diseases, Post-translational modifications, Definition of N-glycosylation, The significance of the extra-cellular location of N-glycosylation, Diagnosis and clinical features of patients with Congenital Disorders of Glycosylation (CDGs), The biochemical mechanisms of normal N-glycosylation, Description of 47 mutations in the N-glycosylation pathway that result in CDG